Análise de critérios de sucesso em Endodontia e Implantodontia - Pereira Júnior, Welington (2009)
The criteria of success in endodontics and implant dentistry were evaluated in longitudinal studies through a systematic review. Bibliographic catalogue sources, electronically identified as MEDLINE (http://www.ncbi.nlm.nih.gov/PubMed), from 1966 until January 19th, and Cochrane Library on the same period, were used. On the searching strategy, the following combination of keywords were used: success criteria and dental implants OR failure criteria and dental implants OR success criteria and osseointegration OR failure criteria and osseointegration OR success criteria and endodontic treatment OR failure criteria and endodontic treatment OR success criteria and root canal treatment OR failure criteria and root canal treatment OR success criteria and endodontic therapy OR failure criteria and endodontic therapy OR success criteria and endodontics OR failure criteria and endodontics. The studies were selected by two independent reviewers that determined the inclusion and exclusion criteria. The search presented 684 related articles, with 263 articles that had no relation with the objective of this work, 206 articles were literature reviews, 378 articles were related with in vivo studies on humans and 14 studies on animals, and 112 were in vitro studies. From the 378 studies on humans, 15 satisfied the inclusion criteria, and all these were related to the success and/or survival of dental implants, with no work that fulfilled the inclusion criteria related to the success of non-surgical root canal treatment. In these studies, it was analyzed the success of 1601 implants with average success rate of 90.84%; the average survival of 5663 implants was 94.7%. It was observed that the investigations used distinct success criteria for the root canal treatments and the dental implants, what implicates the need of adoption of a consensus and actual model, to facilitate the future studies.